Membangun kesadaran kolektif melalui sosialisasi Perubahan ppks menjadi PPKPT di STIE Jayakarta - Oktavia Marpaung; Sita Dewi; Bertha Elvy Napitupulu; Frisca L. Siagian (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
The change in national policy from PPKS (Prevention and Handling of Sexual Violence) to PPKPT (Prevention and Handling of Violence in Higher Education) marks an important milestone in efforts to create a safe, inclusive campus free from all forms of violence. The outreach activities conducted by the STIE Jayakarta PPKPT Task Force represent a tangible form of service to the campus community. This article aims to document the implementation process of these outreach activities and discuss their strategic significance in fostering a campus culture free from violence. A narrative approach is used to convey the dynamics of the activities and their impact on the collective awareness of the academic community. The results of these activities demonstrate an increased understanding of the types of violence as well as the mechanisms for reporting and addressing them. It is hoped that these activities can serve as a model of best practice in promoting the optimal implementation of Ministry of Education, Culture, Research, and Technology Regulation No. 55 of 2024.